To solve the system by substitution, we can set the two equations equal to each other:
-2x = -9x + 21
Now, let's solve for x:
Add 9x to both sides:
7x = 21
Divide by 7:
x = 3
Now that we have found x, we can plug it back into one of the equations to solve for y. Let's use the first equation y = -2x:
y = -2(3)
y = -6
Therefore, the solution to the system of equations is x = 3 and y = -6.
Question
Watch Video
Show Examples
Solve the system by substitution.
y, equals, minus, 2, x
y=
−2x
y, equals, minus, 9, x, plus, 21
y=
−9x+21
Answer
Attempt 1 out of 2
left parenthesis(
,
right parenthesis) Submit Answer
1 answer